Exact travelling wave solutions for the modifed Novikov equation - Deng, Xijun (Nonlinear Analysis: Modelling and Control, 2015)
In this paper, by using the factorization technique and the direct integral method, some exact travelling wave solutions of the modified Novikov equation are obtained. Moreover, our results extend previously known results in the literature.
Keywords: modified Novikov equation; factorization technique; travelling wave solutions